L’expression des valeurs dans une approche cognitive - Kwapisz-Osadnik, Katarzyna (Neophilologica, 2011)
The article deals with the role and the place of axiological elements in contemporary linguistic theories, in particular in cognitive linguistics. With reference to theories underpinning this approach such as pre-conceptual scheme, conceptualisation and categorisation, the author attempts to highlight the presence of values at the experiential level (with this in mind, she suggests analysis of four pre-conceptual schemes: container, part-whole, force and connections), and of further analysis at the level of conceptualisation and categorisation, taking into account social and cultural factors influencing opinion shaping.